PEMANFAATAN BIJI JALI PADA PEMBUATAN OMURICE BERBASIS BAHAN PANGAN LOKAL - Rizqie Auliana, Nancy Okti Setiawati (Prosiding Pendidikan Teknik Boga Busana, 2020)
The aim of this study was to find a recipe for Javanesse Fried Jali Rice in Crepes Pandan with substitution of hanjeli. Tjis type of research uses the R&D (Research and Development) method and the 4D research method in the manufacture of Javanesse Fried Jali Rice in Crepes Pandan to find out the community's appeal to the local food ingredients of the hanjeli. Rhis research is carried out from January 2019 to May 2019. The population of tthis dtudy was the community of PTBB FT UNY and the wider community. The research sample was obtained from 2 expert, 30 semi-trained panelists and 80 untrained panelists. The data collecion method used in this study is a product acceptance test method for consumers. The data tested were qualitative data, then the data were analyzed descriptively. The result of the study were the determination of omurice standart recipe with subtitution of hanjeli by 75%, Javanesse Fried Jali Rice in Crepes Pandan with hanjeli subtitution as local food, P Value T test result between control and development were not significantly different and community acceptence of Javanesse Fried Jali Rice in Crepes Pandan with hanjeli subtitution shows that the product cana be accepted by the wider community. Keywords: Omurice, Hanjeli, Alternative Food